How to improve the provision of global public goods - Kaul, Inge (Archīum Ateneo, 2003)
The studies in the volume suggest that the world is at a turning point in the provision of global public goods. There are many signs of adaptive inefficiency, with institutional change lagging far behind rapidly evolving realities.1 So, even the best-intentioned policies often lead to limited or distorted results. But incipient institutional reforms are discernible: existing molds are becoming brittle, and policymaking and public management patterns are being reconfigured. There is a clear window of opportunity for further change. Based on the analyses in the volume, addressing the following problems seems especially urgent: ● Standard concepts and theories on public goods are inadequate for understanding current realities, capturing the growing phenomenon of global public goods, and providing effective policy guidance. ● Decisionmaking systematically excludes some of those affected by global public goods. ● Financing often comes out of international development assistance. ● The organization of production is compartmentalized and scattered. Most of the chapters’ suggestions on how these problems could be solved build on current reforms and are aimed at nudging forward ongoing change—toward a more adequate provision of global public goods. The case studies, in particular, provide more detailed and issue-specific analyses (see the annex for a brief summary of the case studies). The policy recommendations emanating from the entire volume can be summarized in four parts: refurbishing the analytical toolkit, matching circles of stakeholders and decisionmakers, systematizing the financing of global public goods, and spanning borders, sectors, and groups of actors.